APLIKASI PERAMALAN JUMLAH SISWA BARU DENGAN METODE SINGLE MOVING AVERAGE DI MTS MIFTAHUL ULUM PUNTIR - Muhammad Zainul Anwar; Sigit Setyowibowo (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2023)
The growing importance of education in the modern era is certainly the more prospective students who want to be accepted in the best educational institutions. Therefore, the number of prospective students must be balanced by the number of students that can be accepted by an educational institution. most of the educational institutions have difficulty in predicting the number of prospective students who apply to be difficult also in determining the student received. Making the application of forecasting the number of new students would facilitate the performance of existing human resources. From these observations the researchers make one application model forecasting the number of new students. Forecasting method used is the single moving average method in which the method is based on a projection of the data series are smoothed with a moving average, the value of the data series used are 5 serial data.